Sequential Co-immobilization of Enzymes in Metal-Organic Frameworks for Efficient Biocatalytic Conversion of Adsorbed CO2 to Formate - Li, Yan; Wen, Liyin; Tan, Tianwei; Lv, Yongqin (Frontiers in Bioengineering and Biotechnology, 2019)
The main challenges in multienzymatic cascade reactions for CO2 reduction are the low CO2 solubility in water, the adjustment of substrate channeling, and the regeneration of co-factor. In this study, metal-organic frameworks (MOF) were prepared as adsorbents for the storage of CO2 and at the same time as solid supports for the sequential co-immobilization of multienzymes via a layer-by-layer self-assembly approach. Amine-functionalized MIL-101(Cr) was synthesized for the adsorption of CO2. Using amine-MIL-101(Cr) as the core, two HKUST-1 layers were fabricated for the immobilization of three enzymes chosen for the reduction of CO2 to formate. Carbonic anhydrase was encapsulated in the inner HKUST-1 layer and hydrated the released CO2 to HCO3-. Bicarbonate ions then migrated directly to the outer HKUST-1 shell containing formate dehydrogenase and were converted to formate. Glutamate dehydrogenase on the outer MOF layer achieved the regeneration of co-factor. Compared with free enzymes in solution using the bubbled CO2 as substrate, the immobilized enzymes using stored CO2 as substrate exhibited 13.1-times higher of formate production due to the enhanced substrate concentration. The sequential immobilization of enzymes also facilitated the channeling of substrate and eventually enabled higher catalytic efficiency with a co-factor-based formate yield of 179.8%. The immobilized enzymes showed good operational stability and reusability with a cofactor cumulative formate yield of 1077.7% after 10 cycles of reusing.